THE INFLUENCE OF SNAKEHEAD (CHANNA STRIATA) EXTRACT TREATMENT TO THE MDA LEVEL IN PANCREAS OF HYPERGLYCEMIC RAT (RATTUS NOVERGICUS) - Abdulgani, Nurlita; Hidayati, Dewi; Trisnawati, Indah; Ashuri, Nova; Adinovitasari, Ressy (Acta Scientiae et Intellectus, 2024)
The influence of snakehead (Channa striata) extract (SHE) on the MDA level in hyperglycemic rat (Rattus novergicus) had investigated. Injection of alloxan monohydrate was conducted to induced the hyperglycemic prior to treatment with SHE by oral methods for two weeks. The oxidant capacity of SHE in pancreas were evaluated based on the level of Malondialdehide (MDA). Pancreatic MDA concentration in the group of hyperglycemic rat that was not treated by SHE was in level of 93.96 nmol/ml which significantly higher (p<0.05) than groups of hyperglycemic rat that were treated by SHE in the highest and median dosage i.e. MDA=23.98 nmol/ml and 33.43 nmol/ml, respectively. The lower MDA concentration in the SHE treatment group indicates that SHE therapy can improve the antioxidant capacity resulting the lower levels of free radicals or oxidative stress in pancreas